Association between adolescent sport activities and lumbar disk degeneration among young adults. (19th March 2017) - Takatalo, J.; Karppinen, J.; Näyhä, S.; Taimela, S.; Niinimäki, J.; Blanco Sequeiros, R.; Tammelin, T.; Auvinen, J.; Tervonen, O.
Abstract : The relationship between different sport activities and lumbar intervertebral disk degeneration (DD) is largely unknown. We evaluated whether adolescent participation in different sports is associated with lumbar DD in a population‐based birth cohort of young adults. A total of 558 young adults (325 females and 233 males) underwent magnetic resonance imaging (MRI, 1.5‐T scanner). A DD sum score, based on the Pfirrmann grading, was calculated for all lumbar levels. The sum score was categorized into no DD, 1, 2, or at least 3. Participation in different sport activities was self‐reported by postal surveys at 16, 18, and 19 years, and three groups were formed based on participation frequency in 11 sports: (a) highly active (at least twice a week), (b) moderately active (2‐4 times a month), and (c) inactive (maximum once a month). Cumulative odds ratios (COR) and their 95% confidence intervals (CI) were obtained for each sport by ordinal logistic regression, adjusting for gender, body mass index, age, socioeconomic status, smoking, and other sports. Highly active participation in jogging/running and swimming was associated with a higher DD sum score (COR: 3.0; 95% CI: 1.4‐6.3 and 5.0; 1.7‐15.2, respectively) compared to inactive participation, whereas highly active participation in skating showed low COR. In conclusion, running and swimming at least twice a week in early adulthood are potentially associated with lumbar DD. Follow‐up studies with MRI are needed to show whether frequent exposure to running or swimming has further effect on the integrity of lumbar intervertebral disks.